Systems Thinking in International Education and Development Unlocking Learning for All? - V. Faul, Moira; Savage, Laura (NORRAG Series on International Education and Development, 2023)
The global education crisis is a complex problem that requires change from teachers, school managers, civil society, implementers, planners, governments and donors. Addressing the issues that lie beneath this crisis requires new ways of working. Systems thinking is a suite of approaches to grappling with complex problems that is beginning to gain traction in international education. This book brings together new research in the nascent field of systems thinking in international education. Outlining the implications that systems thinking can hold for future research, practice and progress towards Sustainable Development Goal 4, a diverse range of leading scholars, policymakers and practitioners present novel research to encourage the shift from a linear view of change to a systems view. Chapters present diverse approaches to applying systems thinking in education across middle- and low-income countries, alongside research on how this has changed mindsets more widely. Questioning notions such as scaling and the universal applicability of 'what works', authors here suggest that locally relevant evidence and systemic rewards for using it are necessary to achieve SDG 4. This innovative book exemplifies how systems thinking offers the tools, frameworks and concepts to improve outcomes in education systems. With the education crisis further exacerbated by the COVID-19 pandemic, this timely book is essential reading for all those concerned with education and sustainable development goals. This thought-provoking book should be read by all those working to achieve SDG4; those whose day jobs inspire them and who look to their bookshelves for new ideas.